British and American Chinese children's negotiation of popular cultural texts in bilingual and bicultural contexts - Lin, FangChi (Tiffany) (2009)
This PhD thesis presents an investigation of how British Chinese and American Chinese children, situated in bilingual and bi-cultural context, negotiate the meaning of a popular culture text, Yugioh within their sociocultural practices. The research draws on two theoretical frameworks, reception analysis and New Literacy Studies. Data were collected from surveys, diaries, participant observations and semi-structured interviews with children and parents in the UK and US, over a sixteen-month period from October, 2002 and February, 2004. It is argued that the children’s appropriation of popular culture texts in cross-cultural context is subject to the interwoven effects of a variety of and interconnected situational factors and follows the pattern of product life cycle. In each phase of product life cycle, the children draw on textual and symbolic meanings of Yugioh texts to represent their understandings and interactions with their social world. The analysis shows the textual meanings are used to facilitate the practice of Yugioh activities and literacy learning while the symbolic meanings are to serve different purposes in the children’s socialisation, identity formation and childhood development.